2022
DOI: 10.1002/tcr.202200218
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Nucleobase Modifications in Oligonucleotide Analogues for Use as Environmentally Responsive Fluorophores and Beyond

Abstract: Over the past two decades, it has become abundantly clear that nucleic acid biochemistry, especially with respect to RNA, is more convoluted and complex than previously appreciated. Indeed, the application and exploitation of nucleic acids beyond their predestined role as the medium for storage and transmission of genetic information to the treatment and study of diseases has been achieved. In other areas of endeavor, utilization of nucleic acids as a probe molecule requires that they possess a reporter group.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 115 publications
0
3
0
Order By: Relevance
“…The phenyl‐substituted pC analogues, such as 6‐phenylpyrrolocytidine (PhpC) and boPhpC, are structurally conservative and highly fluorescent cytidine analogues, which are the most commonly used probes for fluorescence‐based assays. [ 92 ] Wahba et al . reported that PhpC‐containing RNA can act as a molecular beacon to report HIV‐1 RT Ribonuclease H activity and has the potential to screen the inhibitors of HIV‐RT RNase H. [ 93 ] The same group also reported that PhpC‐containing small interfering RNAs (siRNAs) can be used to investigate cellular distribution and mechanism of siRNAs.…”
Section: Applications Of Artificial Nucleobases In Molecular Medicinementioning
confidence: 99%
“…The phenyl‐substituted pC analogues, such as 6‐phenylpyrrolocytidine (PhpC) and boPhpC, are structurally conservative and highly fluorescent cytidine analogues, which are the most commonly used probes for fluorescence‐based assays. [ 92 ] Wahba et al . reported that PhpC‐containing RNA can act as a molecular beacon to report HIV‐1 RT Ribonuclease H activity and has the potential to screen the inhibitors of HIV‐RT RNase H. [ 93 ] The same group also reported that PhpC‐containing small interfering RNAs (siRNAs) can be used to investigate cellular distribution and mechanism of siRNAs.…”
Section: Applications Of Artificial Nucleobases In Molecular Medicinementioning
confidence: 99%
“…In order to probe the structure and dynamics of DNA and RNA sequences and their interaction with other biological molecules, structural nucleobase analogues have been developed with high-emission quantum yields. These structural analogues are called fluorescent nucleic acid base analogues (FBAs). A summary of recent developments in the field of FBAs can be found in these articles. Two of the oldest known fluorescent base analogues are 2-aminopurine (2AP) and ethenoadenine (εA), both of which are fluorescent analogues of adenine. 8-Vinyladenine is a relatively new adenine analogue introduced by Mely et al Fluorescent analogues are also known for G, , C, and U. , Besides their use in understanding biological nucleic acid properties, they have also been used in understanding and making synthetic DNA-based devices, such as photoinduced electron transfer through DNA nanowires. New improved FBAs are needed with better single photon and multiphoton emission properties to facilitate single molecule microscopy studies in vitro and in living cells.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, intrinsic nucleobase modifications are done to impart fluorescence properties to the nucleobase while preserving their canonical base-pairing abilities. 4 Surprisingly, it has been found that large number of such intrinsic modifications to the nucleobase gives fluorophores with emissions in the blue region of the visible spectrum 5 and/or are not sufficiently bright for use in real-time applications. For applications in biological systems, it is desirable to have (i) emissions of fluorophores bathochromically shifted from the blue region of the visible spectrum, (ii) practically usable brightness and (iii) environmental sensitivity to changes in the microenvironment.…”
Section: Introductionmentioning
confidence: 99%